PENGEMBANGAN SIKAP SOSIAL SISWA SEKOLAH DASAR MELALUI PEMBELAJARAN KOLABORATIF DAN KERJASAMA TIM - Nurhaeda, Nurhaeda; Putri, Lilis Andika; Fajar, Aldi (Universitas Sulawesi Tenggara, 2023)
Collaborative learning and teamwork in elementary schools have been proven effective in developing students' social attitudes. Through learning activities that encourage students to work together, share ideas, and solve problems together, students not only gain academic skills but also develop positive social attitudes, such as empathy, responsibility, and effective communication. This study aims to examine how collaborative learning and teamwork can play a role in building the social attitudes of elementary school students. The results of this literature study indicate that learning that emphasizes cooperation can improve social relationships between students, reduce conflict, and improve social skills that are useful in everyday life.